Rules for setting off periods of application of measures of procedural coercion in the term of criminal punishment: problems of legislative regulation and law enforcement - Yu. Yu. Ksendzov (Правоприменение, 2022)
The research subject is represented by the correlation between provisions for criminal and criminal procedure law in Russian Federation which turns out to be the basis in resolution of the inclusion of certain terms of criminal procedure measures administration into the criminal punishment duration which is enforced toward a defendant during criminal proceedings.The research objective is expected to be a confirmation or a contestation for hypothesis about the existing diversity of calculation methods for criminal punishment duration. Research methodology encompasses both dialectical and formal cognition methods. It is based on a complex and comprehensive analysis and interpretation of statutory acts, legal reasonings of the Constitutional Court and the Supreme Court of Russian Federation as well as on judicial rulings regarding criminal cases and on doctrinal approaches to the current research subject.Main determinations and application field. The research rationale is represented by the following conclusions. Criminal law does not contain the regulation of the inclusion of certain terms of criminal procedure measures administration into the criminal punishment duration which is enforced toward a defendant during criminal proceedings, namely – the restrictions enforced upon the suspect (defendant) with regards to sub-para. 1 para. 6 of the article 105.1 of the Criminal Procedure Code of Russian Federation. Hence, such issue constitutes an evident legal gap in the existing calculation methods for criminal punishment duration. Given the comprehensive analysis conducted with respect to pre-trial restrictions such as house imprisonment and restraining order, as well as examination of final judicial rulings which concern the inclusion of certain terms of criminal procedure measures administration into the criminal punishment duration which is enforced toward a defendant during criminal proceedings, it can be concluded that the existing case law appears to be generally established. At the same time the judiciary apply rather diversified calculation methods for criminal punishment duration, while due to the absence of distinct and precise legislation judicial provisions being therefore bearable and discordant lead to their controversial interpretation. Moreover, in the author’s opinion, the existing practice for the inclusion of certain terms of pre-trial restrictions administration into the criminal punishment duration does not correlate with such principles of law as principles of justice and equality of citizens in the face of law. Pursuant to the conducted legal research it is suggested to introduce adequate changes and amendments to the effectual criminal law and criminal procedure law accordingly.